The Association between Baseline, Changes in Uric Acid, and Renal Failure in the Elderly Chinese Individuals: A Prospective Study with a 3-Year Follow-Up - Xiuxiu Lai; Bo Gao; Gongmin Zhou; Qingyan Zhu; Yan Zhu; Haijia Lai (International Journal of Endocrinology)
Objective. The objective is to find whether serum uric acid (SUA) levels are associated with the progression of chronic kidney disease (CKD) remains uncertain, and follow-up data among the elderly population are relatively lacking, especially in China. The aim of the present study was to reveal the association between baseline SUA levels, changes in SUA levels, and renal failure in Chinese elderly adults. Methods. In this retrospective cohort study, 425 subjects (age range 71–100 years) were analyzed and divided into quartiles based on baseline SUA levels (Q1: <4.8; Q2: <5.7; Q3: <6.5; and Q4: ≥6.5 mg/dl). CKD was defined as estimated glomerular filtration rate (eGFR) < 60 ml/min/1.73 m2. We used multiple linear and logistic regressions to compare the risk of renal dysfunction among the different SUA level groups. Results. The prevalence of hyperuricemia was 24.24% in the elderly subjects. In the multivariable analysis, the odds ratio (OR) for the development of CKD increased with the increase in SUA quartiles at baseline (1.00 vs. 1.79 (95% CI, 1.00–3.22), 3.4 (95% CI, 1.79–6.47), and 6.79 (95% CI, 3.45–13.75), respectively; P for linear trend <0.001), and a per unit increase in baseline SUA levels gave an OR of 1.76 (95% CI, 1.45–2.14) for renal failure. At the same time, a change in SUA levels had a stronger inverse correlation with a change in eGFR in females (r = −0.318, P<0.001) than in males (r = −0.187, P<0.01). In a linear regression analysis, a 1 mg/dl increase in SUA levels was associated with an additional 1.25 (95% CI, −1.83 to −0.67) ml/min/1.73 m2 decrease in eGFR over a 3-year period. Conclusion. Elevated baseline SUA levels and changes in SUA levels were associated with a decline in eGFR and an increased risk of CKD in an elderly Chinese population.